RANCANG BANGUN SISTEM KENDALI HUMIDIFIER JARAK JAUH BERBASIS MIKROKONTROLER DENGAN IoT (INTERNET OF THINGS) - Zakiyyah, A.Z.; Sumariyah, Sumariyah; Suseno, Jatmiko Endro (BERKALA FISIKA, 2021)
Room conditions that are too dry or too humid are not good for human health, so we need a humidifier that can maintain humidity in the room. There has been no research on humidifiers that apply DHT22 and HC-SR04 sensors and smartphone as device controls. This reasearch is to design of a humidifier that can be controlled from a smartphone with the addition of these two sensors. In this study, the DHT22 sensor was used as a temperature and humidity detector, with a measurement error of 1.5% for temperature and 1.12% for humidity. The HC-SR04 sensor is used to detect the water capacity in the humidifier with a measurement error of 0.48%. The system is made using NodeMCU ESP8266 which can send sensor readings directly to WiFi. The sensor reading results are sent via the internet to the server and then displayed on the Blynk application on the smartphone. In the Blynk application, the desired humidity set point value can be adjusted, and the state of temperature, humidity, and water capacity in the humidifier can be monitored. This Blynk app can display a notification when the water inside humidifier is running low. The system can also display notifications based on set point and detected relative humidity value. If the detected humidity is lower than set point, a notification will appear and humidifier will be automatically turned on. Otherwise if the humidity is higher than set point, a notification will appear and humidifier will be automatically turned off.